Most Likely to Succeed: Six Women from Harvard and What Became of Them - Schumer, Fran. (New York Random House, 1986)
Most Likely to Suceed is a coming-of-age tale-funny, sad, and at times tragic of women who desperately want success.Here are women who analyze averything from their place in the universe to the breakfast cereal they eat, who gauge success by high SAT scores and low weight.
Keywords: Literature